2021
DOI: 10.3390/f12030304
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of Herbivore-Damaged Leaves of Understory Species Growing in Oak and Pine Stands

Abstract: Leaves are the largest component of forest litter. Their decomposition rate depends mainly on plant species, leaf chemical composition, microorganism biodiversity, and habitat conditions. It is known that herbivory by insects can modify the chemical composition of leaves, such as through induction. The aim of this study was to determine whether the rate of leaf decomposition is related to the susceptibility of the plant species to insect feeding and how leaf damage affects this rate. For our research, we chose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Plant secondary compounds are known to vary among tree species and their production responds to both biotic and abiotic stress (Simon & Adamczyk, 2019). Łukowski et al (2021) found that faster decaying leaf litter had a lower content of defensive compounds. Therefore, inhibition of decomposer fungi by secondary plant compounds in green leaf litter remains a viable hypothesis for explaining our results.…”
Section: Discussionmentioning
confidence: 99%
“…Plant secondary compounds are known to vary among tree species and their production responds to both biotic and abiotic stress (Simon & Adamczyk, 2019). Łukowski et al (2021) found that faster decaying leaf litter had a lower content of defensive compounds. Therefore, inhibition of decomposer fungi by secondary plant compounds in green leaf litter remains a viable hypothesis for explaining our results.…”
Section: Discussionmentioning
confidence: 99%